2012
DOI: 10.1007/s10482-012-9810-3
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity of bacterial endophytes of Panax notoginseng with antagonistic characteristics towards pathogens of root-rot disease complex

Abstract: Endophytes play an important role in protection of host plants from infection by phytopathogens. Endophytic bacteria were isolated from five different parts (root, stem, petiole, leaf and seed) of Panax notoginseng and evaluated for antagonistic activity against Fusarium oxysporum, Ralstonia sp. and Meloidogyne hapla, three major pathogens associated with root-rot disease complex of P. notoginseng. From 1000 endophytic bacterial strains evaluated in vitro, 104 strains exhibited antagonistic properties against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 40 publications
3
64
0
Order By: Relevance
“…In the future, we should pay more attention to this genus, for species of Pseudomonas acted as one predicted pathogen causing root-rot disease of P. notoginseng. However, root-rot disease was reported to be caused by number of pathogens including bacteria and fungi (Ma et al 2013), and other common microbial pathogens such as Lonsdalea species can't be ignored, which was also more abundant in rhizosphere soils of diseased plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, we should pay more attention to this genus, for species of Pseudomonas acted as one predicted pathogen causing root-rot disease of P. notoginseng. However, root-rot disease was reported to be caused by number of pathogens including bacteria and fungi (Ma et al 2013), and other common microbial pathogens such as Lonsdalea species can't be ignored, which was also more abundant in rhizosphere soils of diseased plants.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, P. notoginseng is shade cultivated without tillage and is allowed to grow for at least 3 years to develop roots. The long growth period, shaded and humid planting conditions provided suitable environment for the development of several diseases, such as black spot, grey mould, round spot and root rot (Ma et al 2013). Of these diseases, the root-rot disease complex (RRDC) is the most destructive disease affecting P. notoginseng during the whole growth period and could decrease the biological yield by 5-20 %, sometimes exceeding 70 %.…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus is a Gram-positive, spore-forming, rod-shaped genus with high tolerance to adverse ecological conditions. Previous studies have shown that endophytic bacteria of the genus Bacillus are present in: Coffea arabica L. (Vega et al, 2005), sunflower (Forchetti et al, 2007), cotton (Misaghi and Donndelinger, 1990), potato (Sessitsch et al, 2004), strawberry (Dias et al, 2008), Panaxnoto ginseng (Ma et al, 2013), and citrus plants (Araujo et al, 2001). Among the bioprospection factors, the endophyte Bacillus stands out for phosphate solubilization and auxin production (Dias et al, 2008) and activity against Fusarium oxysporum, Ralstonia sp, and Meloidogyne hapla (Ma et al, 2013).…”
Section: Molecular Identification Of Isolates Based On Partial 16s Rdmentioning
confidence: 99%
“…This result is considered as positive for siderophore production, showing the capacity to improve iron nutrition in plants, because siderophores are responsible of chelating and transport 3 , and the ability to fix nitrogen 11 . Similarly, four strains that produced siderophores also showed the ability to inhibit the growth of fungi which was likely due to sequestration of iron by bacteria limiting growth of pathogenic fungus 15 . Isolation of microorganisms that have the ability to inhibit growth of pathogenic fungi could be an alternative to reduce economic losses in agriculture 11 .…”
mentioning
confidence: 99%
“…Percentage inhibition (PI) was calculated using the formula PI = (DC -DT)/DC ď‚´ 100%, where DC and DT represent the colony diameters of Alternaria sp. on the control and treatments respectively 15 . Jojoba is a shrub found in arid zones with rainfall of 80-120 mm/year, temperature ranging from -5ď‚°C to 54ď‚°C and soils with pH 5-8 (ref.…”
mentioning
confidence: 99%